2018
DOI: 10.1038/s41388-018-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel bone morphogenetic protein receptor inhibitor JL5 suppresses tumor cell survival signaling and induces regression of human lung cancer

Abstract: BMP receptor inhibitors induce death of cancer cells through the downregulation of antiapoptotic proteins XIAP, pTAK1, and Id1-Id3. However, the current most potent BMP receptor inhibitor, DMH2, does not downregulate BMP signaling in vivo because of metabolic instability and poor pharmacokinetics. Here we identified the site of metabolic instability of DMH2 and designed a novel BMP receptor inhibitor, JL5. We show that JL5 has a greater volume of distribution and suppresses the expression of Id1 and pTak1 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…4B). DMH2 is similar to JL5, having potent inhibition of BMP type 1 receptors with some inhibition of BMPR2 [8]. DMH2 treated cells also demonstrated an increase in DNA-DSB when used in combination with Ym155 (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…4B). DMH2 is similar to JL5, having potent inhibition of BMP type 1 receptors with some inhibition of BMPR2 [8]. DMH2 treated cells also demonstrated an increase in DNA-DSB when used in combination with Ym155 (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Ym155 decreases BMP signaling H1299 cells were injected into the intradermal space of the anks of NSG mice and were treated with DMSO or JL5 for 4 days. We previously reported that JL5 decreases the expression of Id1 but not XIAP in tumor xenografts [8]. Survivin belongs to the family of anti-apoptotic proteins that have been reported to be regulated by BMP signaling and are known to stabilize the expression of XIAP [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations